2001
DOI: 10.3319/tao.2001.12.2.415(o)
|View full text |Cite
|
Sign up to set email alerts
|

Hydrographic and Satellite Observations of Summertime Upwelling in the Taiwan Strait: A Preliminary Description

Abstract: Combination of the hydrographic and satellite-derived Sea Surface Temperature (SST) data provides new evidence for the existence of four upwelling-related Low Temperature Zones (LTZs) in the Taiwan Strait in summer. These LTZs are located along the southwestern coast of the Tai wan Strait (SW-LTZ), along the northwestern coast of the Taiwan Strait (NW-LTZ), near the Taiwan Bank (TB-LTZ) and around the Penghu Is lands (PH-LTZ), respectively. The hydrographic data from three August cruises during 1997-1999 show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 1 publication
2
26
0
Order By: Relevance
“…Such variability of coastal upwelling can also be demonstrated by a variable hydrographical structure in the sea area near Dongshan with different scale, location, and intensity of low‐temperature and high‐salinity water [ Hu et al ., ]. In addition to interannual variability, two regions of coastal upwelling in the western TWS have clear intermonthly variability in summer [ Hu et al ., ], and the coastal upwelling and cold eddy off Vietnam are punctuated by the intraseasonal oscillation [e.g., Xie et al ., ].…”
Section: Progress Of Upwelling Studies In the China Seasmentioning
confidence: 99%
“…Such variability of coastal upwelling can also be demonstrated by a variable hydrographical structure in the sea area near Dongshan with different scale, location, and intensity of low‐temperature and high‐salinity water [ Hu et al ., ]. In addition to interannual variability, two regions of coastal upwelling in the western TWS have clear intermonthly variability in summer [ Hu et al ., ], and the coastal upwelling and cold eddy off Vietnam are punctuated by the intraseasonal oscillation [e.g., Xie et al ., ].…”
Section: Progress Of Upwelling Studies In the China Seasmentioning
confidence: 99%
“…Summer upwelling near the Penghu Channel southwest of Taiwan (region 4) was also documented (e.g., Hu et al 2001;Hong et al 2011). Past observations (e.g., Hu et al 2001), mainly derived from satellite images, often distinguished the northern extremity of this upwelling (known as the Penghu Island upwelling) from the nearby upwelling along the left banks of the Penghu Channel (known as Taiwan Banks upwelling).…”
Section: Normal Upwelling Before Fanapimentioning
confidence: 99%
“…Past observations (e.g., Hu et al 2001), mainly derived from satellite images, often distinguished the northern extremity of this upwelling (known as the Penghu Island upwelling) from the nearby upwelling along the left banks of the Penghu Channel (known as Taiwan Banks upwelling). In our view the gap may be too small to divide the two.…”
Section: Normal Upwelling Before Fanapimentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Tang et al 7 found the high pigment concentrations along the western coast of the TS in winter through the CZCS-derived pigment data. Hu et al 8 combined the hydrographic and NOAA/AVHRR SST data to detect the summer upwelling in the TS. Tang et al 9 coupled the SeaWiFS-derived Chl-a and NOAA/AVHRR SST data to locate the summer upwellings in the TS.…”
Section: Introductionmentioning
confidence: 99%